1987
DOI: 10.1152/ajpgi.1987.252.6.g797
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance spectrophotometry for the assessment of gastroduodenal mucosal perfusion

Abstract: Reflectance spectrophotometry in assessing gastroduodenal mucosal perfusion was evaluated. Ischemia without congestion, e.g., during hemorrhagic hypotension or celiac artery occlusion, was associated with a reduction in the indexes of mucosal hemoglobin concentration and of oxygen saturation. Ischemia with congestion, e.g., during portal vein occlusion, or in absolute ethanol or suction-induced mucosal lesions, was associated with an increase in the index of mucosal hemoglobin concentration but a reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…The mHbO 2 values reported are the means of the last 5 min (150 spectra, 2 s each) of the respective intervention under steady state conditions. This method allows detection of splanchnic ischemia with similar precision as laser flowmetry (Leung et al 1987), intra-vital microscopy (Bellamy et al 1997), or hydrogen gas clearance (Machens et al 1995). The non-traumatic instrumentation and in particular nontraumatic access to the gastric mucosa allows the determination of mucosal oxygenation in the absence of surgical stress.…”
Section: Measurementsmentioning
confidence: 99%
“…The mHbO 2 values reported are the means of the last 5 min (150 spectra, 2 s each) of the respective intervention under steady state conditions. This method allows detection of splanchnic ischemia with similar precision as laser flowmetry (Leung et al 1987), intra-vital microscopy (Bellamy et al 1997), or hydrogen gas clearance (Machens et al 1995). The non-traumatic instrumentation and in particular nontraumatic access to the gastric mucosa allows the determination of mucosal oxygenation in the absence of surgical stress.…”
Section: Measurementsmentioning
confidence: 99%
“…38 On the other hand, despite raising systemic blood pressure to the same extent as in the rats with PPVL, glybenclamide did not alter portal pressure in rats with SO. The observation suggests that K ϩ ATP channels play a role in regulating portal pressure possibly only in the presence of a stimulus to elevate portal pressure, e.g., after PPVL, which produces ischemia with congestion in the gastric mucosa 39 and reduces perfusion to the liver initially. We speculate that the hypoxic stimulus to both the stomach and liver triggers the opening of K ϩ ATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…With this system, the largest values of IHb and ISO2 can be obtained be cause the pressure on the gastric mucosal capillaries by the sensor tip decreases IHb and ISO2; and when the tip of the sensor does not touch the gastric mucosa, the reading of IHb and ISO2 decreases. Using the reflect ance spectrophotometry system, Leung et al reported that IHb increased and ISO2 decreased when the portal vein was ligated, and IHb and ISO2 decreased when the celiac artery was occluded in anesthetized rats (14). The former therefore indicated mucosal congestion and the latter indicated ischemia.…”
Section: Discussionmentioning
confidence: 99%